The evolving role of national parliaments in the European Union : Ireland as a case study - Barrett, Gavin (Manchester University Press, 2018)
The evolution in parliaments' roles, the reasons for this and the challenges that lie in wait for future progress are all considered, with Ireland's stop-start parliamentary adaptation, the role of the Lisbon Treaty and economic crises in accelerating reform carefully analysed.